Marketing Communications Tool for Feedback Towards Domestic Tourist’s Decision on Bangkok Area Tourism - Taninoot Ngourungsi ธนินนุช เงารังษี; Mallika Polanan มัลลิกา ผลอนันต์ (Dusit Thani College Journal, 2018)
The objectives of this research were studying the co-relationship between marketing communication tools consisting of advertisement, public relations, directed marketing, staff service, and sale promotion. Making decision on domestic tour of Bangkok tourists. The data gathering was done by using related questionnaire for 200samples. Analyzing The data analysis applied regression analysis called MMR (Multi-variable Multiple Regression) together with Pearson’s Co-efficiency to examine the corelationship of marketing communication tools. In conclusion, all independent variables resulted on the subset of dependentvariables. Accessingmedia to the targeted group effectively by using marketing communication tools and statistics in the research.